An Analysis upon the Contribution of Romanticism to Modernism in the Work of W.B. Yeats: The Influence of Romanticism on W.B. Yeats' Transition to Modernism (Journal of Advances and Scholarly Researches in Allied Education, 2016)
One is continually helped to remember the way that Yeats was one of the considerable modern masters whose significance and intrigue are guaranteed forever. However in a general investigation of Yeats as a poet almost no accentuation is given to his Irish foundation and to his political idea. Frequently focus is saved for his specialty and theory.This examination fundamentally centers around the Romantic poet William Butler Yeats' poem Sailing to Byzantium so as to exhibit Romanticism's commitment to the supposed modernist movement as far as idealism. A while later, it keeps up Yeats as a Romantic Modernist and Sailing to Byzantium for instance to Yeats' progress from Romanticism to Modernism. At long last, it finishes up by proclaiming the way that albeit each of the three works were composed in various years, they have various similitudes that constitute their essential principles.